General Ordinances of the City of Aspen, § 125, in Aspen Daily Times, Jul. 27, 1886, at 3-6 - (:unkn) unknown (My University, 1886)
No person shall keep at his place of business or elsewhere within this city, a greater quantity of gun powder or gun cotton than fifty pounds at one time, and the same shall be kept in tin or copper canisters containing not to exceed ten pounds in each.§
Keywords: GUNPOWDER - STORAGE